Early Specialization and Progress of Finalist Swimmers in World Championships and Olympic Games - Inmaculada Yustres Amores; Jesús Santos del Cerro; Víctor Rodrigo Carranza; Francisco Hermosilla-Perona (Journal of Functional Morphology and Kinesiology)
Background: The main objectives of this study were to analyze the effect of early specialization in swimming and to observe the general patterns of success of two different sport specialization models [Spanish (SPA) and United States of American (USA) swimmers] participating in World Championships (WCs) and Olympic Games (OGs) between the years 2006 and 2021 of all swimming strokes and distances. Methods: Descriptive analyses and contingency tables were examined for all the variables. Explanatory models of the z scores were estimated from age depending on the events’ distances and strokes. Quadratic regression models were developed to capture the behavior of the variable time with parabolic functions, and the significance of the global model and the predictor variables (age) were also evaluated. In addition, the optimal age (peak performance) as well as the curvature of the model were analyzed. These models were compared between SPA and USA swimmers. Results: The results showed that the main differences in the patterns to success between SPA and USA were the earlier participation of USA swimmers in high-level competitions, as well as the greater number of participants for all the strokes, events, genders, and competitions. Age peak performance in short distances was lower for Spanish swimmers, obtaining the opposite situation for long distances. Conclusions: Being a finalist in junior WCs did not influence success in the finals of the senior WCs and OGs. Main differences in general patterns of success between SPA and USA showed younger swimmers participating in short-distance events, backstroke, and butterfly for USA swimmers and older swimmers taking part in butterfly and short-distance events for SPA.